Dynamic Responses of Calving Caribou to Oilfields in Northern Alaska - Haskell, Shawn P.; Nielson, Ryan M.; Ballard, Warren B.; Cronin, Matthew A.; McDonald, Trent L. (ARCTIC, 2009)
Past research has suggested that during the calving period, caribou (Rangifer tarandus) in Arctic Alaska generally avoid areas within 1 km of oilfield roads with traffic. However, avoidance is not absolute, and caribou may habituate to infrastructure (e.g., buildings, roads, well pads) and human activity. We conducted road-based surveys of caribou in oilfields on Alaska’s Arctic Coastal Plain during the late calving and post-calving periods of June in 2000–02. We recorded location, composition, and behavior of caribou groups located less than 1 km from active gravel roads and production pads. Caribou groups with calves were on average distributed farther from oilfield infrastructure than were groups without calves, but habituation to oilfield activities, indicated by decreased avoidance, occurred at similar rates for groups with and without calves. During the calving period, sighting rates were greater in areas of low human activity, and calf percentages tended to be greater at night when oilfield activity was reduced. Caribou groups were on average closer to infrastructure during the post-calving periods than during the calving periods in 2000 and 2001, but not in 2002. In 2002, when snow melted early, caribou groups were closer to infrastructure during the calving period than in 2000 and 2001, when snow melted later, emphasizing the importance of examining environmental variables when investigating the dynamic interactions of caribou and oilfields. Overall, caribou appeared to habituate to active oilfield infrastructure after the calving period in 2000, late in the calving period in 2001, and likely before our sampling period in 2002. The timing of annual rehabituation was positively correlated with timing of spring snowmelt. Land and wildlife managers can use information from this study to develop calving period-specific mitigation measures that are more effective and flexible. Selon des recherches antérieures, pendant sa période de vêlage, le caribou (Rangifer tarandus) de l’Alaska arctique évite ...